Formulation and Evaluation of Red Betel Leaf (Piper crocatum L) Ethanol Extract 96% in Anti-Acne Cream - Pratiwi, Yani; Azis, Asyari Al Hutama; Dilla, Nurfarah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Acne (Acne vulgaris) is a common skin problem experienced, especially by teenagers and young adults, which can lower self-esteem. One causes is bacteria Propionibacterium acnes and Staphylococcus epidermidis. Red betel leaves (Piper crocatum L) are known to contain active compounds such as flavonoid, tannins, alkaloid, and essential oil that effective as antibacterial and anti-inflammatory agents. The aim of this study is to formulate and evaluate a topical cream containing a 96% ethanol extract of red betel leaves (Piper crocatum L.) as an anti-acne preparation. This study employed a laboratory experimental approach, formulating an oil-in-water (O/W) type cream by varying the concentrations of the emulsifiers stearic acid and triethanolamine (TEA). The physical properties of the cream were assessed through organoleptic evaluation, homogeneity testing, pH measurement, spreadability, adhesion, viscosity, cream type identification, and mechanical stability testing. The results that formula IV with an extract concentration of 12.5%, stearic acid 17%, and TEA 3.5% produces the most optimal results, with stable physical characteristics, homogeneous, and meeting topical cosmetic standards. Thus, 96% ethanol extract cream of red betel leaf has potential to be used as alternative treatment for acne based on natural ingredients.